Chemical compounds and antibacterial activity of Garcinia dulcis (Roxb)kurz. - Hady Anshory Tamhid (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Garcinia dulcis is a medicinal plant used traditionally to treat various diseases including infections of wounds and ulcers. The antibacterial activity of this plant has also been widely reported, but the most potent compounds as an antibacterial agent are not widely reported, even though the compounds contained in this plant is well known. This paper reviews the compounds contained in G. dulcis plants and their potential as antibacterial agents. Each part of this plant, such as leaves, fruits, flowers, seeds, stems, and roots, contains secondary metabolites which are potential antibacterial agents. Here are described the compounds contained in each part of the plant, such as xanthones, the most dominant compounds, then flavonoids, benzophenones, chromones, and triterpenoid. Their antibacterial activity is also described, especially those that have strong activity against bacteria. The molecular structure and the possibilities of how the antibacterial mechanism are also discussed.  Eleven compounds that have the potential to be used as antibacterial agents for the treatment of infectious diseases. Garcigerin A (27) and a-mangostin (54) are compounds that have the most vigorous activity against S. aureus and MRSA compared to the other compounds. The Compounds that have strong activity can be used as antibacterial agents for anti-infective therapy, although they must go through various further studies.